Peripheral Arterial Disease Treatment in the Non-Hospital Setting - Wiechmann, Bret N. (Seminars in Interventional Radiology, 2023)
Treatment of peripheral artery disease (PAD) has undergone a progressive shift toward less invasive, endovascular options within the last three decades. For PAD patients, the benefits of this shift are numerous and include less periprocedural pain, decreased blood loss, shorter recovery times, and fewer missed workdays. Commonly, patient-reported outcomes are very positive with this “endovascular first” strategy and the number of open surgical procedures for various stages of PAD has declined steadily over the last 20 years. Coincident with this trend is the move toward “ambulatory” lower extremity arterial intervention (LEAI) in the hospital outpatient “same-day” department. The next logical extension was then performing LEAI in a true physician office-based lab (OBL), ambulatory surgical center (ASC), or “non-hospital setting.” This article examines these trends and the concept that the OBL/ASC provides a safe, alternative site of service for PAD patients requiring LEAI.
Keywords: peripheral artery disease; office-based lab; ambulatory surgical center; interventional radiology